VALUING OFFSHORE NATURAL GAS DEVELOPMENT PLAN THROUGH REAL OPTIONS: CASE STUDY OF INDONESIA - Nur Kemala, Prodia
Over a decade, more than 50% discoveries in Indonesia is dominated by natural gas. In replacing more polluting fossil fuel, natural gas plays an important role as bridge to low carbon future during energy transition. Despite the government set ambitious target to achieve 12 BCFD gas production by 2030, natural gas lifting realization only 6 BCFD by 2023. This research aims to valuate an offshore natural gas development plan of major oil and gas Production Sharing Contract (PSC) in Indonesia as one of national gas supply backbone. Given that the domestic gas market is highly regulated and influenced by policy, uncertainties will continue to exist. In this circumstance, using Discounted Cash Flow (DCF) method is not adequate to evaluate natural gas development given static and single point input with no volatility and uncertainty estimated used. Hence, this research uses the extension of DCF method, namely Real Options Valuation (ROV) with sequential compound options for multiple phase model. This research proved that ROV delivers higher investment valuation compared to DCF method due to the presence of options value which closely related to managerial flexibility and strategic options. We argue that despite ROV offering a substantial and helpful point of view on scenarios selection, ROV analysis solely is not sufficient. This research is the first research of ROV application using in the Final Investment Decisions (FID), which identifies the interrelationship among three dependent variables e.g. volatility factor, gas price and Take or Pay (TOP) volume. This research analyzes the combined impact of these key variables during robustness check and advanced sensitivity analysis to validate and evaluate the stability of the best development scenario selected to any changes in key variables. By understanding the degree to which different gas prices and TOP structures affect the project valuation, more favorable commercial terms that aligned with project sanction could be secured during gas sales negotiation with gas buyers. This research shows that the best scenario could fall to second or third ranking under two conditions: (1) both volatility and implementation cost increase; and (2) volatility increase while gas price and TOP decrease. This research features an insight for stakeholders in energy sector in valuating investment using ROV decision framework for Indonesia case study.